Analisis Fenomena Warung Madura 24 Jam Dalam Perspektif Solidaritas dan Pembangunan Ekonomi Modern di Desa Tegalboto, Sumbersari, Jember. - Adil Fihukmi Farqi; Yuzicha Nindia Safira Revizal; Wisnu Aji; Tiara Putri Maulida (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
24-hour Madura stalls have become part of the economic life of local communities in many cities in Indonesia. This research aims to analyze the role of 24-hour Madura food stalls in strengthening local community solidarity while adapting to the dynamics of modern economic development. Warung Madura 24 hours plays an important role in strengthening local community solidarity by providing employment opportunities for local communities and being a vital place for social interaction. However, Madura stalls have their own challenges, namely competition between modern stalls and minimarkets that offer similar products on a larger scale. In our research we concluded that 24-hour Madura warungs have a significant role in strengthening local community solidarity while remaining relevant in modern economic development.